Penerapan Artificial Intelligence Pada Kotak Amal Masjid Dan Mushalla Sebagai Security System Berbasis Radio Frequency Identification - Defnizal, Defnizal; Ernes, Risa Nadia (Politeknik Ganesha Medan, 2020)
The high crime rate in Indonesia has had a bad impact and loss on society, so that various efforts have been made to increase awareness and security in society. Charity box theft is a target of crime for criminals. For this reason, it is necessary to take strict steps in terms of vigilance and security so that the crime of theft of charity boxes can be avoided. One of the steps to increase awareness and safety is to apply the concept of security to the charity box. By utilizing several supporting sensors and supporting components in the charity box, the security system will work automatically, so that if there is a charity box theft, the system will provide an SMS notification to the mosque management. This research is focused on the problem of security facilities and supervision of charity boxes in mosques or mushalla. Using this system will reduce the risk of theft of charity boxes in mosques and mushalla, because apart from being equipped with an alarm and SMS gateway, this system is also equipped with RFID so that access to open charity boxes can be safer. This form of system works if the charity box is lifted or dismantled by force, the system will provide notification in the form of an alarm and SMS, so that the crime of theft of the charity box can be more aware of.